ANALISIS DETERMINAN KEPATUHAN ORANG DENGAN HIV/AIDS DALAM KONSUMSI OBAT ANTIRETROVIRAL (ARV) DI PUSKESMAS BATU ANAM KABUPATEN SIMALUNGUN. - Afrilius Simanjuntak; Roni Monica Purba; Viktor Edyward Marbun; Mona Fitri Gurusinga (Jurnal Penelitian Kesmasy, 2023)
The success of HIV/AIDS treatment is strongly influenced by compliance to antiretroviral (ARV) consumption. This study aims to analyze the factors that determine the compliance of people with HIV/AIDS in consuming antiretroviral drugs (ARV) at Batu Anam Health Center. The research design used was cross-sectional. The population in the study was 179 people with a sample of 123 people. The sampling technique is using the purposive sampling method. The results of the bivariate analysis showed that the variables that influenced compliance were age (p=0.040) and peer community support (p=0.016), while the variables that did not affect compliance were gender (p=0.489), education level (p=0.314), status marriage (p=0,764), length of therapy (p=752), knowledge (p=0,272), attitude (p=0,272), health insurance (p=0,509) and access to health services (p=1,000). The results of multivariate analysis showed that the variable that most influenced compliance was peer community support with an Exp (B) of 4.00 (95%CI 1.006-15.897) meaning that PLWHA who received good support from their peer community had 4,000 times more chance of compliance to ARV treatment. greater than PLWHA who do not receive good support from the peer community. It is suggested to the STI/VCT/CST HIV service at Batu Anam Health Center in order to increase cooperation with the HIV peer community to increase PLWHA compliance in ARV consumption at Batu Anam Health Center.